Association of intracortical myelin and cognitive function in bipolar I disorder. (13th March 2018) - Sehmbi, M.; Rowley, C. D.; Minuzzi, L.; Kapczinski, F.; Steiner, M.; Sassi, R. B.; Bock, N. A.; Frey, B. N.
Abstract : Objective: Although cognitive dysfunction persists through affective and euthymic states in bipolar disorder (BD), its neurobiological correlates remain undetermined. We explore whole‐cortex intracortical myelin (ICM) and cognition in BD‐I and controls. Methods: T1 ‐weighted images (3T) optimized for ICM measurement were analyzed using a surface‐based approach. MRI signal was sampled at cortical mid‐depth. Cognitive performance was measured via standardized computerized battery and paper‐and‐pencil Trails B. Results: ICM was associated with verbal memory (VM) in BD throughout a cortical network identified with pertinence to VM function, with strongest effects in left caudal middle temporal cortex and left dorsolateral prefrontal cortex ( P corrected  < 0.05). Subanalyses revealed specific association with correct word recognition, without delay. Processing speed, executive function, and reaction time were also predicted by ICM in BD, but not controls, although this did not survive Bonferroni correction. Conclusion: This is the first study to show VM association with ICM in BD. ICM has been implicated in the integrity of neural connections and neural synchrony. VM dysfunction is one of the most replicated cognitive abnormalities in BD. Therefore, these results provide a novel mechanism for understanding cognitive dysfunction in BD, which can aid in the development of targeted therapeutics to improve cognitive outcomes in BD.